THE SCIENTIFIC RESEARCH LEVEL ON THE PROBLEM OF PSYCHOLOGICAL STABILITY AND FINANCIAL STRESS (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the impact of psychological stability and financial stress on economic decisions from the perspectives of economic psychology and behavioral economics. The study examines an individual's psychological state, particularly their level of stress resilience and decision-making characteristics under financial pressure. Additionally, an empirical analysis was conducted on the differences in financial status assessment and risk appetite levels between students of economics and psychology.
Keywords: Psychological stability, financial stress, economic decisions, economic psychology, behavioral economics, risk, risk appetite, stress resilience, financial literacy, economic behavior, coping strategies, psychoeducation